(untitled) (Al-Academy, 2025)
Biological art is considered one of the contemporary and innovative arts, with its experimental and interactive mediums that explore the intersections of biological sciences and draw from those developments to stimulate and enrich the artistic experience with a level of expression that may challenge social, cultural, and ethical references. It requires direct experimentation on living organisms of various kinds. The artistic creations emerge from laboratories after collaborative experimental processes with scientists and researchers, carrying the strangeness of aesthetic pleasure of the event. They are accompanied by audience stimulation within an educational and awareness strategy. These creations are the result of interactive introductions between contemporary scientific references that branch out into a wide network of sciences, extending their roots towards engineering, chemistry, physics, and information technology. The current research sheds light on the most impactful and contributing scientific references to enrich the experiences of biological art.